Hazard Quotient Association of SO2 Exposure to Respiratory Symptoms: Study on Scavengers in Sarimukti Landfill, West Bandung Regency, East Java, Indonesia - Tina Shinta Parulian; Yura Witsqa Firmansyah; Susanti Niman (Journal of Epidemiology and Public Health, 2025)
Background: The WHO reported that airborne diseases were responsible for 39 million deaths, accounting for 57% of the total 68 million deaths worldwide in 2021. Landfills are a significant source of air pollution, producing sulfur dioxide (SO2) gas, which is harmful to respiratory health, particularly the lungs. This study aims to examine the relationship between the hazard quotient of SO2 exposure and respiratory symptoms among scavengers at the Sarimukti landfill in West Bandung Regency, using an environmental health risk analysis approach.Subjects and Method: The research contributes to exposure risk management by establishing safe thresholds for SO2 concentration, exposure time, and frequency for scavengers. This study adopts a correlation design with a longitudinal approach. The sample consisted of 101 scavengers selected through accidental sampling. Pollutant measurements were taken at two locations within the Sarimukti landfill. The independent variable in this study is the hazard quotient value of SO2 expo-sure, while the dependent variable is respiratory symptoms in scavengers.Results: The results indicated a (OR= 15.83; 95% CI= 1.10 to 226.67; p= 0.008). Risk management is based on a safe SO2 concentration limit of 14.18 µg/m³, an exposure time of 15 hours, and an exposure frequency of 637 days over 30 years.Conclusion: The measurement result of SO2 concentration of 7.38 µg/m³ is still below the specified quality standard of 150 µg/m³. However, through the calculation of the hazard quotient, the concentration exceeds the safe limit (HQ >= 1). The implication of this study in preventing the occurrence of respiratory symptoms in waste pickers is the use of PPE, limiting working hours and days in the landfill.